Evaluating Learner Performance: It's Complicated - Jeff Pettit; Kristi Ferguson (Association of American Medical Colleges, 2014)
Abstract Evaluating learners is a critical component of education. Distinguishing between feedback and evaluation, identifying the impact of the evaluation system, and recognizing that evaluation may be serving multiple purposes are not always considered by evaluators. This workshop is designed to clarify many of the issues surrounding evaluation and how evaluators can become more effective. This workshop was conducted at multiple sessions in different regions in the state of Iowa. Sessions were between 1 and 1.5 hours in length. The workshop evaluation responses follow a scale of 1 (low) to 5 (high) and were completed by 102 participants. When asked whether the educational activity improved their skills, average response rate for the evaluation items were as follows: (1) Distinguish between feedback and evaluation and understand why it is an important distinction [4.51]; (2) Identify the impact of the evaluation context/system on a particular evaluation [4.24]; (3) Recognize that evaluations may be serving multiple purposes [4.43]; and, (4) Describe factors that contribute to effective evaluations [4.37]. The average response rate for the remaining session evaluation items were: (1) The information presented will be useful in my teaching of residents and students [4.33]; (2) The format of this activity was appropriate to the information being presented [4.34]; (3) The style of presentation used by the instructor(s) was effective [4.44]; (4) The quality and use of graphics and visuals was appropriate [4.35]; and, (5) My interest in this topic has been stimulated by the instructor(s) [4.27].